2016
DOI: 10.1136/neurintsurg-2016-012668
|View full text |Cite
|
Sign up to set email alerts
|

A rare but morbid neurosurgical target: petrous aneurysms and their endovascular management in the stent/flow diverter era

Abstract: Endovascular treatment of large or symptomatic petrous ICA aneurysms, in the era of flow diversion, is associated with excellent angiographic and clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…There are only 25 cases that are reported the outcomes of cranial nerve after the treatment 12,13,19,24,25,30,41,44,46,48,54,55,59,61,72,88 . Regarding the analyses of different treatments, there are only a few reports 9,13,14,19,83 on PA patients treated with a flow diverter stent. We think that the number of studies reporting the use of a flow diverter will increase in the future, and this difference may aid in elucidate the treatment effects of flow diverter and parent artery occlusion or entrapment.…”
Section: Treatment Strategies and Results From Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…There are only 25 cases that are reported the outcomes of cranial nerve after the treatment 12,13,19,24,25,30,41,44,46,48,54,55,59,61,72,88 . Regarding the analyses of different treatments, there are only a few reports 9,13,14,19,83 on PA patients treated with a flow diverter stent. We think that the number of studies reporting the use of a flow diverter will increase in the future, and this difference may aid in elucidate the treatment effects of flow diverter and parent artery occlusion or entrapment.…”
Section: Treatment Strategies and Results From Literature Reviewmentioning
confidence: 99%
“…To direct treatment strategies for cranial nerve palsy due to PAs in the future, we conducted a literature review of previously reported cases 6,7,[9][10][11][12][13][14][15][16]19,20,[24][25] . We searched for all reported case studies and clinical research papers regarding PAs that were published in English.…”
Section: Systematic Reviewmentioning
confidence: 99%
See 3 more Smart Citations